DNA repair of oxidative DNA damage in human carcinogenesis: Potential application for cancer risk assessment and prevention - Paz-Elizur, Tamar; Sevilya, Ziv; Leitner-Dagan, Yael; Elinger, Dalia; Roisman, Laila C.; Livneh, Zvi (Cancer letters, 2008)
Efficient DNA repair mechanisms comprise a critical component in the protection against human cancer, as indicated by the high predisposition to cancer of individuals with germ-line mutations in DNA repair genes. This includes biallelic germ-line mutations in the MUTYH gene, encoding a DNA glycosylase that is involved in the repair of oxidative DNA damage, which strongly predispose humans to a rare hereditary form of colorectal cancer. Extensive research efforts including biochemical, enzymological and genetic studies in model organisms established that the oxidative DNA lesion 8-oxoguanine is mutagenic, and that several DNA repair mechanisms operate to prevent its potentially mutagenic and carcinogenic outcome. Epidemiological studies on the association with sporadic cancers of single nucleotide polymorphisms in genes such as OGG1, involved in the repair of 8-oxoguanine yielded conflicting results, and suggest a minor effect at best. A new approach based on the functional analysis of DNA repair enzymatic activity showed that reduced activity of 8-oxoguanine DNA glycosylase (OGG) is a risk factor in lung and head and neck cancer. Moreover, the combination of smoking and low OGG activity was associated with a higher risk, suggesting a potential strategy for risk assessment and prevention of lung cancer, as well as other types of cancer.